Meet the Leader interview with H.E. Benjamin Mkapa third President of the Republic of Tanzania - UONGOZI Institute (Dar es Salaam UONGOZI Institute, 2012)
Meet the Leader is honoured to meet the third president of Tanzania, H.E. President Benjamin Mkapa. His efforts included the creation of an open forum called the Presidential Commission on Corruption (Warioba Commission). He also privatised state-owned corporations and instituted free market policies. His policies won the support of the World Bank and International Monetary Fund and resulted in the cancellation of some of Tanzania's Foreign debts.
Keywords: Leadership